See things for what they are: Examining the financial condition on financial reporting quality in developed countries - Kristantie, Amarissa Ayoe; Manullang, Tanti Winda Asrani; Nugroho, Albertus Henri Listyanto; Christanti, Rossalina (Journal of Accounting and Investment, 2026)
Research aims: This study aims to determine the relationship between the Company's financial condition and the quality of financial reports.Design/Methodology/Approach: The classification of financial conditions in this study utilises the Altman Z-score model, which categorises companies into three categories: green zone, grey zone, and red zone. Researchers tested the hypothesis using the Generalised Least Squares (GLS) method to accommodate differences in data characteristics, heteroscedasticity, and multicollinearity diagnostic problems on 58,890 company-year observations from 47 developed countries between 2014 and 2023.Research findings: The results of this study support the hypothesis that a company's financial condition plays a role in determining the quality of its financial reports. Companies in the green zone and grey zone categories strive to maintain the quality of their financial reports and encourage an improvement in the quality of these reports. Meanwhile, companies in the red zone category tend to embellish the appearance of their financial report performance to conceal financial difficulties, which ultimately have the potential to compromise the quality of their financial reports.Theoretical contribution/Originality: This study offers insight into the implications of financial conditions on the quality of corporate financial reports in the international context of developed countries, which exhibit more advanced economic, social, and legal conditions.Research limitation/Implication: This research has practical implications for investors, creditors, external auditors, and regulators, as it suggests using bankruptcy zone assessment as an early warning system to evaluate the quality of financial reports.